The Covalent Modification of Proteins: New Therapeutics and Probing Function and Mechanism - Dornan, Mark (Université d'Ottawa / University of Ottawa, 2016)
Covalent bond-forming reactions between small molecules and proteins are ubiquitous. These reactions play a central role in the diversification and functionalization of proteins, enabling normal cell growth and life. Scientists routinely employ electrophilic compounds to modify proteins by exploiting the intrinsic nucleophilicity found on amino acid side-chains. These modifications permit a wide variety of experiments and allow for new insights and a deeper understanding of the chemistry and biology of living systems. The three research projects described in this thesis employ electrophilic, protein-modifying agents to meet unique goals. The first study (Chapter 2) details the development of a novel class of compounds that enhance the efficacy of therapeutic oncolytic viruses specifically in cancer cells. A medicinal chemistry-based approach was used to understand, measure and improve physicochemical and pharmacological properties of these small molecules. Inspired by the unique scaffold identified in Chapter 2, the second study of this thesis (Chapter 3) explores the bioactivity of the structurally related armeniaspirole natural products. Chemical synthesis enabled the uncovering of structure-activity relationships and ultimately allowed for the design of an activity-based probe. The final study (Chapter 4) details investigations of the terminal thioesterase involved in the biosynthesis of valinomycin. Small molecules substrates for the enzyme were synthesized and used to reveal details of the enzymatic mechanisms.
Keywords: Medicinal chemistry; Chemical biology